Design Exploration Study of Exhaust System Mixer for Emission Performance - Salim Koc; Tetsuo Nohara; Nobuyuki Suzuki; Kazuhiro Nakamura; Taiki Matsumura; Shotaro Udagawa; Daisaku Haruki (International Journal of Automotive Engineering, 2018)
SCR systems are mainly used in exhaust systems as an emission control device for diesel engines with excellent thermal efficiency. In this paper we explored the design of mixing devices which are an important element in the system. The optimum shape for various conditions and designs to disperse ammonia from a urea solution was optimized with CAE and design space exploration, and validated with visualization experiments for correlation.